Minimal patient handling: a faculty of prehospital care consensus statement. Issue 12 (14th November 2013) - Moss, R; Porter, K; Greaves, I; ,
Abstract : This paper outlines the emerging best practice when packaging a prehospital trauma patient while providing spinal immobilisation. The best practice described is based on the recommendations of a consensus meeting held by the Faculty of Pre-Hospital Care, Royal College of Surgeons of Edinburgh, in the West Midlands in April 2012, where the opinion of experienced practitioners from across the prehospital and emergency care community considered the currently available evidence and reviewed current clinical practice. Initial consensus points were then subject to further review and dialogue with stakeholders from the initial meeting. The recommendations drawn from the meeting and subsequent dialogue represent a 'general agreement' to the principles and practices described in the paper. The recommendations will provide guidance for clinical practice and governance alongside other consensus statements from the Faculty of Pre-Hospital Care that seek to address prehospital spinal immobilisation and pelvic immobilisation.